1987
DOI: 10.1677/joe.0.1140173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on renal responsiveness to parathyroid hormone and calcitonin in rats

Abstract: The purpose of these studies was to determine whether the responsiveness of the kidney to parathyroid hormone (PTH) and calcitonin changed with age. Experiments were performed in young (3 months old), adult (12-14 months old) and old (22-24 months old) male Fischer 344 rats fed normal diets and thyroparathyroidectomized. Parathyroid hormone was administered i.p. at 24, 12 and 2 h before death and calcitonin was given i.p. at 12 and 2 h before death. Parathyroid hormone significantly increased the conversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In rats, with maturation and aging, the capacity of PTH to stimulate renal 1,25(OH) 2 D production also declines. Specifically, the capacity of the kidney to increase plasma 1,25(OH) 2 D in response to PTH given in vivo declines with age [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, with maturation and aging, the capacity of PTH to stimulate renal 1,25(OH) 2 D production also declines. Specifically, the capacity of the kidney to increase plasma 1,25(OH) 2 D in response to PTH given in vivo declines with age [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, Paget's disease patients treated with etidronate had higher 1,25(OH) 2 D 3 levels without significant changes in serum PTH, ionized calcium, or phosphate [85,500]. Lawson-Matthew et al [501] found increased 1,25(OH) 2 D 3 concentrations following shortterm oral etidronate treatment but decreased 1,25(OH) 2 D 3 levels after high-dose intravenous etidronate.…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…The inhibition of intestinal 24-hydroxylase activity and expression may spare 1,25(OH) 2 D 3 from deactivation and thereby result in enhanced l,25(OH) 2 D 3 -mediated activity [84]. The majority of in vitro data have supported the positive effect of calcitonin on 1,25(OH) 2 D 3 levels [85,86]. Similar to in vivo data, 1a-hydroxylase was stimulated by calcitonin in vitamin-D-deficient rat kidneys, post-TPTX [86].…”
Section: Calcitoninmentioning
confidence: 99%
“…The extent of these age-related alterations are similar in adult (10-12 months) and old (18-24 months) rats of the Fischer 344 strain. In addition, the production of CAMP and 1,25(OH),D3 in renal slices are decreased in response to PTH in aging animals (Armbrecht et al, 1986(Armbrecht et al, , 1987.Kiebzak and Sacktor (1986) examined the phosphate transport in intact and parathyroidectomized (PTX) rats fed a low phosphate diet. They found that the agerelated decrease in adaptation to a low phosphate regime persisted in PTX animals.…”
mentioning
confidence: 99%